Key maturity indicators for module libraries for PLC-based control software in the domain of automated Production Systems. Issue 11 (2018) - Vogel-Heuser, Birgit; Fischer, Juliane; Neumann, Eva-Maria; Diehm, Sebastian
Abstract: As module libraries in PLC-based control application in automated Production Systems (aPS) are the key to more efficient engineering, the quality maturity of these modules should be measurable. Such maturity indicators help to convince application engineers and start-up personnel to use existing modules instead of re-inventing the wheel, resulting in huge savings of money and time. This paper proposes quality metrics for such module libraries and their visualization for the domain of aPS.